PENGARUH GERAKAN 3M PLUS TERHADAP KEBERADAAN JENTIK NYAMUK AEDES AEGYPTI DI RW 01 KEPENGHULUAN MELAYU BESAR KECAMATAN TANAH PUTIH TANJUNG MELAWANAN - Azzah Rawani; Elda Nazriati; Sofia Anita (Jurnal Ilmu Lingkungan, 2018)
Research has been conducted in Kepenghuluan Melayu Besar Subdistrict Tanah Putih Tanjung Melawan in January to February 2018. The aim of this research was to analyze the indicator of the presence of Aedes aegypti mosquito larvae on 3M Plus movement in Kepenghuluan Melayu Besar Subdistrict Tanah Putih Tanjung Melawan and analyze the effect of 3M Plus movements and impacts socio-economic on the existence of Aedes aegypti mosquito larvae in Kepenghuluan Melayu Besar Subdistrict Tanah Putih Tanjung Melawan. The results showed that 3M Plus movement affected to decrease larva population in an area. The impact of the 3M Plus movement was viewed from an economic aspect, namely the costs incurred was cheaper than before the 3M Plus movement. The social impact gained from 3M's movement Plus the empathy and feeling of mutual cooperation in the community, the use of recycled goods increases the aesthetic value because the use of used goods to be used as crafts, feeling safe and comfortable and not panicking when there is an attack of DHF and the emergence of clean living behavior and healthy in the community.